3 sonatas pour piano dédiées au célèbre J. Haydn par L. van Beethoven ... op. 2, no. 3. - Beethoven, Ludwig van, 1770-1827 (composer):::Creator:::::::::::: (France; S. Richault; Paris, 2022)
Early edition of the Piano Sonata no. 3 in C minor, op. 2, no. 3, published in Paris by S. Richault.